Anatomy of Income and Wealth Inequality in the United States - Muczyk, Jan; Coccari, Ronald (Journal of Comparative International Management, 2015)
Much has been written recently about the current income and wealth gaps in the U.S. and the causes proffered. They are: how U.S. elections are financed; offshoring of well-paid jobs; excessive executive salaries; decrease in private-sector unionization; inadequate education of the U.S. workforce; and the outsize return on capital. The authors assume that these are merely the visible manifestations of a larger underlying cause — "The Iron Law of Oligarchy." They identify the oligarchs, describe how they rule and the consequences, and propose ways to ameliorate the consequences.